Challenging the therapeutic narrative - Goldstein, Robert G., author.
1 online resource.
Keywords: "This volume explores and challenges the assumption that behavioral proclivities and pathologies are directly traceable to experience-an assumption that still widely dominates folk psychology as well as the perspective of many mental health practitioners. This tendency continues despite powerful evidence from the field of behavioral genetics that genetic endowment dwarfs other discrete influences on development and psychopathy when extrinsic conditions are not extreme. An interdisciplinary collection, the book uses historical, cultural and clinical perspectives to challenge the longstanding notion of identity as product of a life-narrative. Although the nativist-empiricist debate has been revivified by recent advances in molecular biology, such ideas date back to the Socratic dialogue on the innate mathematical sense possessed by an illiterate slave. The author takes a philosophical and historical approach in revisiting the writings of select figures from science, medicine and literature whose insights into the potency of inherited factors in behavior were particularly prescient, and ran contrary to the modern declivity toward the self as narrative. The final section of the volume uses historical and clinical perspectives to help illuminate the elusive concept of innateness, and ultimately highlights important ramifications of the revolution in behavioral genetics. Seeking to challenge the clinical utility of the therapeutic narrative rather than the importance of experience per se, the book will ultimately appeal to psychiatrists, psychologists, and academicians from various disciplines working across the fields of behavioral genetics, evolutionary biology, philosophy of science and the history of science"--